MARKETING STRATEGY TO INCREASE SALES OF WATER TREATMENT PRODUCTS AND SERVICES - Brilian Novianti, Fitri
Water demand is increasing along with the growth of industries and the waste generated. However, water needs are not balanced by an increase in water supply, so water availability is very limited. Therefore, it is a great opportunity for water treatment companies to make a profit. However, PT BLUE OCEAN experienced a decline in sales, which means that PT BLUE OCEAN could not take advantage of this opportunity as well as possible. This study aims to analyze the external and internal environment and propose marketing strategies following the company's resources and capabilities to increase sales of PT BLUE OCEAN. External environmental analysis is carried out using PESTLE, Porter's Five Forces, consumer analysis and competitor analysis. Consumer analysis is done by in-depth interviews. To analyze the interview results from consumer analysis, the author uses content and thematic analysis to determine what factors support PT BLUE OCEAN's marketing strategy. From the analysis of the company's external environment, opportunities and threats outside the company's environment can be found that can affect PT BLUE OCEAN's business. In addition, internal environmental analysis was carried out using RBV analysis, marketing mix analysis, and VRIO. From the company's internal environment analysis, the company's strengths and weaknesses were found. Furthermore, the results of the external and internal environment analysis are used for a SWOT analysis. The SWOT analysis is carried out by combining the findings from the company's external and internal analysis, namely the strengths, weaknesses, opportunities, and challenges, which are then used to make the TOWS matrix. Several alternative marketing strategies will be generated through the TOWS matrix, which will then be selected as the most suitable strategy according to the company's resources and capabilities to increase sales.